Ubiquitin‐specific protease 28 deubiquitinates TCF7L2 to govern the action of the Wnt signaling pathway in hepatic carcinoma. Issue 10 (11th August 2022) - Sun, Xiao; Cai, Mengjiao; Wu, Lingzhi; Zhen, Xinghua; Chen, Yuetong; Peng, Jin; Han, Suxia; Zhang, Pumin
Abstract: Overexpression of ubiquitin‐specific protease 28 ( USP28 ) is found in hepatic carcinoma. It is unclear whether the deubiquitinase plays a role in hepatocarcinogenesis. Deregulation of the Wnt signaling pathway is frequently associated with liver cancer. Transcription factor 7‐like 2 (TCF7L2) is an important downstream transcription factor of the Wnt/β‐catenin signaling pathway, but the mechanisms by which TCF7L2 itself is regulated have not yet been revealed. Here, we report that USP28 promotes the activity of the Wnt signaling pathway through maintaining the stability of TCF7L2. We further show that FBXW7 is the E3 ubiquitin ligase for TCF7L2. By regulating the levels of TCF7L2, USP28 modulates the Wnt/β‐catenin signaling in liver cancer and USP28 depletion or inhibition by a small molecule inhibitor leads to a halt of growth in liver cancer cells. These results suggest that USP28 could be a potential therapeutic target for liver cancer. Abstract : we reported that USP28 promotes the activity of the Wnt signaling pathway through maintaining the stability of TCF7L2. We further showed that FBXW7 is the E3 ubiquitinatin ligase for TCF7L2. By regulating the levels of TCF7L2, USP28 modulates the Wnt/β‐catenin signaling pathway in liver cancer. As a result, liver cancer cells are sensitive to USP28 depletion or inhibition by a small molecule inhibitor. Our results suggest that USP28 could be a potential therapeutic target for liver cancer.